Hypogonadism in opioid using males in an inner-city cohort: A cross-sectional study - Wehbeh, MD, Leen; Dobs, MD, MHS, Adrian S.; Brown, MD, PhD, Todd T. (Journal of Opioid Management, 2021)
Objectives: The link between male hypogonadism and opioids is well-established, but whether there is a difference in the frequency of hypogonadism between heroin and methadone for treatment of opioid use disorder (OUD) has not been determined. Design: Cross-sectional. Setting, patients, and participants: Male drug users and nonusers matched for socioeconomic status between 18 and 65 years, recruited in Baltimore as part of the study of HIV, injection drug use, nutrition, and endocrinology (SHINE). Methods: Hypogonadism was defined as low free testosterone <50 pg/mL. Participants were categorized into three groups based on opioid use: (1) NONE, (2) methadone use as treatment of OUD (METHADONE), and (3) Heroin use (HEROIN). This third group was further divided to mild (MH), and heavy (HH) heroin use. We used multiple logistic regression to examine the association between hypogonadism and different groups. Results: The cohort consisted of 189 men, 94 percent black, average age 43 years, with high HIV (56 percent) and HCV (38 percent) prevalence. 24 percent had hypogonadism. Compared to NONE, there were higher odds of hypogonadism in METHADONE (aOR 3.46; 95 percent CI [1.34,8.93]; p = 0.01) but not in HEROIN. After dividing HEROIN into MH and HH, there were higher odds of hypogonadism in HH compared to NONE (aOR 3.27; 95 percent CI [1.12,9.53]; p = 0.03) but not in MH. Conclusions: Methadone used for treatment of OUD was associated with male hypogonadism similar to heavy heroin use. Targeted hypogonadism screening and treatment may be warranted in this population to reduce its health consequences such as sexual dysfunction, osteoporosis, and abdominal adiposity.